Single centre prospective study of the efficacy of percutaneous cement augmentation in the treatment of vertebral compression fractures. (August 2013) - Joseph, R. N.; Swift, A. J.; Maliakal, P. J.
Abstract: Introduction . Despite controversial outcomes of recent published trials, percutaneous cement augmentation remains widely used in managing painful vertebral compression fractures. We prospectively assessed patients with such fractures using an eleven-point visual analogue scale for pain and the Qualeffo 41 questionnaire for quality of life. Methods. Consecutive patients undergoing percutaneous cement augmentation for painful vertebral compression fractures were recruited. Patients were assessed pre-procedure by completing a visual analogue scale for pain, on a scale of 0 to 10. A Qualeffo 41 questionnaire was also completed. Patients were followed up at 1 week and 3 months. Results. Fifty six patients were prospectively recruited (111 vertebroplasty and 5 kyphoplasty). Visual analogue scores dropped from 6.4 ± 2.3 pre-procedure to 4.0 ± 2.7 at 1 week (p < 0.0001) and 4.3 ± 2.7 (p < 0.0001) at 3 months. Three subgroups were identified; osteoporotic patients (n = 28), a second non-osteoporotic group (n = 20) who had acute fracture following fall and a third group with compression fractures secondary to metastatic disease (n = 8). At 3-month follow-up, patients with osteoporotic fractures had reduction in pain score from 6.3 ± 2.1to 4.8 ± 2.7 (p = 0.02). Patients who had traumatic fractures experienced more significant pain relief, 6.4 ± 2.6 to 3.8 ± 2.7 (p = 0.0009) but patients with malignant fracture had most benefit, 6.0 ± 3.0 to 1.8 ± 0.8 (p = 0.01). Total Qualeffo scores improved from 63 ± 15 to 49 ± 22 (p < 0.0001). Within the domains of the Qualeffo questionnaire, most improvement was seen in pain and physical function. Median in-patient stay post procedure was one day. Conclusion . In our experience percutaneous cement augmentation is safe and efficacious in the management of painful VCF related to osteoporosis, trauma and cancer, achieving rapid and significant pain reduction and improvement in physical function as measured with a visual analogue scale and the Qualeffo 41 questionnaire.